Techno-Economic Analysis of the placement of the Capacitor in the Integrated Nepal Power System - Thakuri, Manisha Shahi; Darlami, Hari Bahadur (Advances in Engineering and Technology: An International Journal, 2021)
With the increasing load demand, Integrated Nepal Power System (INPS) is facing a stiff challenge to maintain voltage profile within the standards and reduce system loss. Among the loss reduction strategies, an immediate solution would be installation of reactive power compensators at the grid substations. The power flow study of existing system is performed and a genetic algorithm is used to find optimum placement of suitable size of the capacitor banks to be added in system. 6 substations with a total reactive power supply of 80 MVAR was determined as optimal size and location and the installation is also financially feasible. Moreover, the analysis of capacitors placed at the varying voltage levels implied that the most suitable voltage level for the capacitor installation is 11kV.